The Concept of Gestational Diabetes Mellitus and Its Treatment (Eurasian Medical Research Periodical, 2023)
The article deals with the diagnosis and treatment of diabetes mellitus in pregnant women. The importance of phytotherapy in the complex treatment of gestational diabetes mellitus and the prevention of its complications is discussed. Phytotherapy in combination with a diet can effectively correct carbohydrate metabolism and reduce the dose of insulin and synthetic antidiabetic drugs.